2012
DOI: 10.1103/physrevb.85.054430
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic levitation of metamaterial bodies enhanced with magnetostatic surface resonances

Abstract: We propose that macroscopic objects built from negative-permeability metamaterials may experience resonantly enhanced magnetic force in low-frequency magnetic fields. Resonant enhancement of the timeaveraged force originates from magnetostatic surface resonances (MSRs), which are analogous to the electrostatic resonances of negative-permittivity particles, well known as surface plasmon resonances in optics. We generalize the classical problem of the MSR of a homogeneous object to include anisotropic metamateri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Such resonant force is result of surface plasmon resonances at the boundary between air and substrate 16 . This resembles the high forces that arise using magnetostatic surface resonances for levitation of metamaterials 22 . Ideally, this resonance can result in an arbitrarily large force acting on the dipole, but as is typical with resonant phenomena, it is limited in practice by the losses.…”
Section: As a Function Of The Height Over The Substrate (Vertical Aximentioning
confidence: 99%
“…Such resonant force is result of surface plasmon resonances at the boundary between air and substrate 16 . This resembles the high forces that arise using magnetostatic surface resonances for levitation of metamaterials 22 . Ideally, this resonance can result in an arbitrarily large force acting on the dipole, but as is typical with resonant phenomena, it is limited in practice by the losses.…”
Section: As a Function Of The Height Over The Substrate (Vertical Aximentioning
confidence: 99%
“…Achieving low permeability while keeping, at the same time, low weight of the structure, can be quite helpful to facilitate magnetic levitation, 17 and the array of conductive rings considered in this work appears to be suitable for such use. Also, with the lowest nonresonant magnetic permeability considered so far, this analysis may pave a road towards the so-called MNZ (permeability near zero) materials.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no natural materials, exhibiting strong diamagnetic response at room temperature, it has been recently shown that certain metamaterials can be characterized by effective magnetic permeability μeff0 in a considerably wide frequency range , and the effect of the magnetic levitation of macroscopic objects over the surface of such metamaterials has been predicted . Generally, the study of electromagnetic forces both at macro‐ and micro level has become a rapidly growing research area in recent years …”
Section: Introductionmentioning
confidence: 99%